Penerapan Stategi Pembelajaran Berbasis Permainan Untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas VIII SMP - Dwi Putri Yanti; Puji Rahayu; Moh Syadidul Itqon (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to describe and measure the effectiveness of implementing a game-based learning strategy in improving mathematics learning outcomes for eighth-grade junior high school students. Mathematics is often perceived as difficult and boring, leading to decreased student interest and learning outcomes. A game-based learning strategy was chosen because it can create a fun learning environment and increase student motivation and learning activities. This classroom action research (CAR) was conducted at Nurul Jadid Junior High School with 20 students, using two cycles encompassing planning, implementation, observation, and reflection. The results showed an increase in the average grade from 73.75 in cycle I to 82.5 in cycle II, as well as an increase in the percentage of students completing the course from 55% to 70%. This indicates that the game-based learning strategy is effective in improving students' mathematics learning outcomes.